Mechanical characteristics of aluminium alloy joints produced by friction stir welding. (2022) - Sivakumar, C.K.; Robinson, Y.; Prema, P.; Joe Patrick Gnanaraj, S.; Appadurai, M.
Abstract: Friction stir welding of AA6061-T6 specimen is conducted for different sets of welding parameters and the elements are analyzed to determine the mechanical properties like hardness, tensile strength, micro structural properties and chemical composition. The set of welding parameters varied are tool rotations per minute, tool feed per min, load/pressure applied on weld. The tool used is H13 on frictional stir welding machine and weld type selected is butt weld on 6 mm sheets of AA6061-T6. Tensile test is conducted in M30 universal testing machine, and the hardness test is conducted in MSM model hardness tester for Rockwell hardness. The after-welding test results are compared against before welding properties of the material. On an average 75% of the mechanical properties are found to be matching with the original material properties.